2016
DOI: 10.1007/398_2016_9
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Metal Pollution in Pakistan and Its Possible Risks to Public Health

Abstract: Environmental pollution has increased many folds in recent years and in some places has reached levels that are toxic to living things. Among pollutant types, toxic heavy metals and metalloids are among the chemicals that pose the highest threat to biological systems (Jjemba 2004). Unlike organic pollutants, which are biodegradable, heavy metals are not degraded into less hazardous end products (Gupta et al. 2001). Low concentrations of some heavy metals are essential for life, but some of them like Hg, As, Pb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 109 publications
2
30
0
3
Order By: Relevance
“…We observed that patients intoxicated with Pb presented SBP similar to control patients. However, we detected an increase in diastolic and mean blood pressure in Pb-intoxicated patients, which is in accordance with previous reports in literature showing increases in blood pressure following Pb-intoxication in humans [ 8 , 51 – 55 ]. As H 2 S has been shown to have several actions in cardiovascular system, we investigated the levels of H 2 S in plasma from patients and found decreased plasmatic H 2 S levels in patients from Pb-intoxicated group.…”
Section: Discussionsupporting
confidence: 93%
“…We observed that patients intoxicated with Pb presented SBP similar to control patients. However, we detected an increase in diastolic and mean blood pressure in Pb-intoxicated patients, which is in accordance with previous reports in literature showing increases in blood pressure following Pb-intoxication in humans [ 8 , 51 – 55 ]. As H 2 S has been shown to have several actions in cardiovascular system, we investigated the levels of H 2 S in plasma from patients and found decreased plasmatic H 2 S levels in patients from Pb-intoxicated group.…”
Section: Discussionsupporting
confidence: 93%
“…This indicates that long-term exposure to HPF poses a health risk due to overexposure to copper. Copper is a microelement, but overexposure to this essential mineral has been reported to predispose the consumer to gastrointestinal mucosal ulcerations and bleeding, hepatic necrosis, coma, cardiotoxicity, hypotension [44], leukaemia and cancer [45]. Cd and Hg contents, on the other hand, were well below the MRL limits for all the 6 HPs.…”
Section: Resultsmentioning
confidence: 99%
“…Забруднення навколишнього природного середовища важкими металами стало глобальною проблемою. До головних факторів, що спричинили загрозливий стан довкілля, відносять застарілу технологію виробництва у промисловості, несучасне обладнання, низький рівень упровадження ресурсо-та енергозаощаджувальних, екологічно чистих технологій; високий рівень концентрації промислових об'єктів; відсутність належних природоохоронних систем; низький рівень експлуатації існуючих природоохоронних об'єктів; відсутність належного правового та економічного механізмів регулювання; прогресуючу урбанізацію населення, розростання гігантських мегаполісів, відсутність належного контролю за охороною довкілля, виверження вулканів (Davydova, 2005;Shakir et al, 2017).…”
Section: вступunclassified